(untitled) (Baltic Journal of Sport and Health Sciences, 2022)
Background: The ACSL A/G single nucleotide polymorphism is associated with endurance trainability. It was previously demonstrated that AA carriers had a reduced maximal oxygen consumption (VO2 max) in response to training compared to GG carriers, and that this polymorphism explained 6.1% of the variance in the VO2 max response to training. The aim of the present study was to determine the prevalence of the ACSL A/G polymorphism among soccer players. Methods: One hundred and sixty-seven male athletes (60 soccer players, 48 sprinters and jumpers, 59 long distance runners) and 60 non-athletic controls participated in the study. Genomic DNA was extracted from buccal epithelial cells using standard protocol for ACSL genotyping. Results: The prevalence of the ACSL AA genotype was significantly higher among soccer players (35%) compared to controls (12%), sprinters and jumpers (15%) and long-distance runners (15%). The findings suggest that despite the importance of aerobic capacity for soccer performance, the prevalence of ACSL AA carriers – a genotype that was related to reduced endurance trainability – is significantly higher among soccer players compared to endurance and power athletes and controls. This genetically unfavorable predisposition should be considered when selecting the team squad and when planning fitness training modalities throughout the competitive season. Keywords: sprinters, long-distance runners, soccer players, ACSL genetic polymorphism.